2008
DOI: 10.1262/jrd.20088
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Expression and Localization of X-linked Inhibitor of Apoptosis Protein (XIAP) in Follicular Granulosa Cells During Atresia in Porcine Ovaries

Abstract: Abstract. Follicular selection predominantly depends on granulosa cell apoptosis in porcine ovaries, but the molecular mechanisms regulating the induction of apoptosis in granulosa cells during follicular selection remain incompletely understood. To determine the role of X-linked inhibitor of apoptosis protein (XIAP), which suppresses caspase-3, -7 and -9 activities and acts as an endogenous inhibitor of apoptotic cell death, in the regulation of granulosa cell apoptosis during follicular atresia, we examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 52 publications
2
18
0
1
Order By: Relevance
“…This localisation change, however, did not occur in sheep, highlighting potential variation in XIAP expression patterning in relation to atresia in ruminants and rodents (Phillipps et al 2011). A decrease in XIAP mRNA and protein expression levels has been observed with increasing atresia as determined by in situ TUNEL and changes to antral follicular fluid ratios of 17b-oestradiol (E 2 )/progesterone in porcine ovarian follicles (Cheng et al 2008). Furthermore, a proportion of sheep antral follicles present during the follicular phase show decreasing XIAP expression levels with increasing active caspase-3 immunoreactivity (Phillipps et al 2011).…”
Section: Xiap Roles In the Ovarymentioning
confidence: 89%
See 2 more Smart Citations
“…This localisation change, however, did not occur in sheep, highlighting potential variation in XIAP expression patterning in relation to atresia in ruminants and rodents (Phillipps et al 2011). A decrease in XIAP mRNA and protein expression levels has been observed with increasing atresia as determined by in situ TUNEL and changes to antral follicular fluid ratios of 17b-oestradiol (E 2 )/progesterone in porcine ovarian follicles (Cheng et al 2008). Furthermore, a proportion of sheep antral follicles present during the follicular phase show decreasing XIAP expression levels with increasing active caspase-3 immunoreactivity (Phillipps et al 2011).…”
Section: Xiap Roles In the Ovarymentioning
confidence: 89%
“…In rats, XIAP is present in granulosa cells, thecal tissue and oocytes within follicles from the preantral stage onwards (Li et al 1998). Moreover, subsequent studies in pigs and sheep have confirmed granulosa and thecal cell expression in antral follicles (Cheng et al 2008, Phillipps et al 2011. In sheep, XIAP has been detected at the protein level early in development in primary staged follicles up to large antral follicles (Phillipps et al 2011).…”
Section: Inhibitor Of Apoptosis Proteinsmentioning
confidence: 91%
See 1 more Smart Citation
“…The vast majority of follicles undergo atresia at various stages of development. Follicular atresia in pigs is regulated by many factors (Kimura et al, 1999;Wada et al, 2002;Matsuda-Minehata et al, 2005;Maeda et al, 2007;Cheng et al, 2005Cheng et al, , 2008Matsuda et al, 2008;Sugimoto et al, 2010). Manabe et al (2004) summarized five apoptosis signaling pathways and emphasized the importance of three cell death ligand-receptor systems, TNF-TNFR, Fas L-Fas, and TRAIL-TRAILR.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported [19,20], total RNA was extracted from cells using a QIAshredder and RNeasy Mini Kit (Qiagen, Chatsworth, CA, USA) according to the manufacturer's directions. First strand cDNA was synthesized from the total RNA using a Ready-To-Go T-Primed First-Strand Kit (GE Healthcare, Little Chalfont, UK).…”
Section: Reverse Transcription-polymerase Chain Reaction (Rt-pcr) Assmentioning
confidence: 99%